The history and philosophy of technology (University of Illinois Press, 1979)
History and philosophy of science is seen as a useful approach in secondary education, then the history and philosophy of technology has an equal claim. The history of technology has often been seen as the poor relation of the history of science, yet its study can not only support the learning of scientific principles, but also engage students in a debate about contemporary and often contested technological issues – from the ‘information revolution’ to climate change. From this point of view, technology is much more than applied science. Certainly, scientific principles are involved, but even in its ‘purest’ form, technology is more about designing artefacts and systems than understanding the natural world. This significant difference is reflected in the sort of models that technologists use for design. Even where the underlying mathematics of a technological model may be identical to a related scientific one (differential equations, Fourier transforms, for example), the way the models are elaborated and used within a technological or engineering culture is usually very different from the comparable scientific context.